The mechanical effects of CRT promoting autophagy via mitochondrial calcium uniporter down‐regulation and mitochondrial dynamics alteration. Issue 6 (2nd April 2019) - Yu, Ziqing; Gong, Xue; Yu, Yong; Li, Minghui; Liang, Yixiu; Qin, Shengmei; Fulati, Zibire; Zhou, Nianwei; Shu, Xianhong; Nie, Zhenning; Dai, Shimo; Chen, Xueying; et al.
Abstract: The mechanism of cardiac resynchronization therapy (CRT) remains unclear. In this study, mitochondria calcium uniporter (MCU), dynamin‐related protein‐1 (DNM1L/Drp1) and their relationship with autophagy in heart failure (HF) and CRT are investigated. Thirteen male beagle's dogs were divided into three groups (sham, HF, CRT). Animals received left bundle branch (LBB) ablation followed by either 8‐week rapid atrial pacing or 4‐week rapid atrial pacing and 4‐week biventricular pacing. Cardiac function was evaluated by echocardiography. Differentially expressed genes (DEGs) were detected by microarray analysis. General morphological changes, mitochondrial ultrastructure, autophagosomes and mitophagosomes were investigated. The cardiomyocyte stretching was adopted to imitate the mechanical effect of CRT. Cells were divided into three groups (control, angiotensin‐II and angiotensin‐II + stretching). MCU, DNM1L/Drp1 and autophagy markers were detected by western blots or immunofluorescence. In the present study, CRT could correct cardiac dysfunction, decrease cardiomyocyte's size, alleviate cardiac fibrosis, promote the formation of autophagosome and mitigate mitochondrial injury. CRT significantly influenced gene expression profile, especially down‐regulating MCU and up‐regulating DNM1L/Drp1. Cell stretching reversed the angiotensin‐II induced changes of MCU and DNM1L/Drp1 and partly restored autophagy. CRT's mechanical effects down‐regulated MCU, up‐regulated DNM1L/Drp1 and subsequently enhanced autophagy. Besides, the mechanical stretching prevented the angiotensin‐II‐induced cellular enlargement.